Interface treatment method of magnesium battery negative electrode material
By spin-coating the interface treatment layer of materials such as tetrapyrrole compounds on the surface of the negative electrode of the magnesium battery, the problems of uneven deposition, corrosion and reaction during the charging and discharge of the negative electrode of the magnesium battery are solved, and the cycle stability and energy density of the battery are significantly improved.
Patent Information
- Application Number
- CN202510062365.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
AI Technical Summary
During the charging and discharging process, the negative electrode of the magnesium battery often faces problems such as uneven deposition of magnesium metal, surface corrosion and reaction with the electrolyte, which leads to a degradation of battery performance, especially the cycle stability and energy efficiency, which is difficult to meet the requirements of high-performance batteries.
The negative electrode of the magnesium battery is prepared in one step by spin coating. By mixing the tetrapyrrole compound, binder and organic solvent, spin-coated on the surface of the negative electrode of the magnesium battery, and drying the solvent to form a stable interface treatment layer.
Significantly improve the electrochemical performance of magnesium negative electrode, enhance the cycle stability, energy density and safety of magnesium batteries, extend the cycle life of the battery and improve energy efficiency.
Smart Images

Figure CN119864372A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of secondary energy storage batteries, and in particular to an interface treatment method for a negative electrode material of a magnesium battery. Background Art
[0002] In recent years, with the increasing demand for green energy, magnesium batteries, as a new type of high energy density, low cost and environmentally friendly energy storage technology, have received widespread attention. Magnesium batteries use magnesium metal as the negative electrode material. Compared with traditional lithium batteries, magnesium batteries have higher theoretical specific capacity and more abundant resources, better safety and lower cost. Therefore, the development of high-performance magnesium battery negative electrode materials, especially in terms of electrochemical stability, cycle life and rate performance, has become the key to the widespread application of magnesium battery technology. However, the negative electrode of magnesium batteries often faces problems such as uneven magnesium metal deposition, surface corrosion and reaction with the electrolyte during the charging and discharging process. These problems lead to a decrease in battery performance, especially the battery's cycle stability and energy efficiency are difficult to meet the requirements of high-performance batteries.
[0003] In order to solve this problem, researchers have improved the electrochemical performance of magnesium negative electrode surfaces by interfacial modification. Optimization of the negative electrode interface can effectively improve the deposition and dissolution behavior of magnesium metal, reduce hydrogen evolution reaction, reduce corrosion, and improve the cycle stability of the battery. Currently commonly used interface modification methods include adding interface protection layers, metal coatings, polymer protective films, and functional compound coatings. In particular, organic functional coatings have been widely studied and applied due to their low cost and good controllability. Tetrapyrrole compounds, as a typical organic compound, have good conductivity, chemical stability, and excellent electron transport properties, and have been widely used in the functional modification of battery electrode materials. They significantly improve the performance of electrode materials by forming a stable electronic environment and reducing side reactions on the metal surface.
[0004] However, the existing tetrapyrrole compounds used for battery interface modification have insufficient affinity with the electrode surface and are difficult to form a stable interface modification layer, which can cause the modification layer to fall off or fail, affecting the overall performance of the battery. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides an interface treatment method for magnesium battery negative electrode materials. The magnesium battery negative electrode of the present invention is prepared in one step by spin coating, which has low cost, few preparation process steps, simple operation and is suitable for large-scale promotion and production.
[0006] The technical solution of the present invention is as follows:
[0007] 1. A method for treating an interface of a negative electrode material of a magnesium battery, characterized in that the method comprises mixing a tetrapyrrole compound, a binder and an organic solvent to obtain an interface treatment material, evenly spin-coating the interface treatment material on the surface of the negative electrode of the magnesium battery, and then drying the solvent.
[0008] The surface mentioned here refers to the side facing the positive electrode.
[0009] Preferably, the negative electrode of the magnesium battery includes magnesium foil, aluminum foil, copper foil, magnesium alloy, or carbon-based materials; the tetrapyrrole compound includes one or more of phthalocyanine compounds, porphyrin compounds, and synthetic tetrapyrrole compounds.
[0010] More preferably, the phthalocyanine compound includes one or more of copper phthalocyanine, iron phthalocyanine, aluminum phthalocyanine, nickel phthalocyanine, and zinc phthalocyanine.
[0011] More preferably, the porphyrin compound includes one or more of heme, chlorophyll, cobalt porphyrin, and magnesium porphyrin.
[0012] More preferably, the synthetic tetrapyrrole compound includes one or more of dimethylphthalocyanine, aromatic tetrapyrrole compound, and bimetallic porphyrin.
[0013] Preferably, the binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol, polyurethane, polyacrylic acid, polytetrafluoroethylene, hydroxypropyl methylcellulose, gelatin, alginate, polyvinyl alcohol-polyvinyl pyrrolidone, and polystyrene-polymethacrylate.
[0014] Preferably, the organic solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, 1,4-dioxane, and acetonitrile.
[0015] Preferably, the concentration of the tetrapyrrole compound in the organic solvent is 5-10 mmol / L.
[0016] Preferably, the mass ratio of the tetrapyrrole compound to the binder is (5-10):1.
[0017] Preferably, the coating thickness of the interface treatment material on the surface of the negative electrode of the magnesium battery is 5-50 μm.
[0018] When the magnesium negative electrode prepared by the above method is used to assemble a magnesium battery, the electrolyte used is APC, MACC, Mg(CF 3 SO 3 ) 2 Based electrolyte and Mg(TFSI) 2 One of the base electrolytes.
[0019] The beneficial technical effects of the present invention are:
[0020] 1. The present invention can significantly improve the electrochemical performance of the magnesium negative electrode by coating a tetrapyrrole compound coating on the surface of the magnesium foil. Tetrapyrrole compounds, especially phthalocyanine and porphyrin compounds, have good electrochemical activity and strong metal ion coordination ability, and can form an effective protective film on the surface of the magnesium negative electrode. The tetrapyrrole compound coating has inherent hydrophobicity, which can protect the underlying magnesium metal from water intrusion and subsequent passivation, and the tetrapyrrole compound coating provides the negative electrode with better conductivity, thereby well homogenizing the charge distribution. In addition, the tetrapyrrole compound further enhances the stability and conductivity of the magnesium foil during the charge and discharge process by optimizing the electronic conduction at the electrode interface, thereby improving the overall performance of the magnesium battery.
[0021] 2. In the present invention, by adjusting the tetrapyrrole compound coating, the battery interface properties can be finely controlled. The aromatic rings and metal ion coordination properties of these compounds can effectively form strong and stable chemical bonds with the magnesium metal surface, forming an efficient electron conduction channel, thereby improving the conductivity and cycle stability of the magnesium battery. In addition, tetrapyrrole compounds have strong antioxidant properties and chemical stability, which can effectively inhibit the reaction between the magnesium metal surface and the active ingredients in the electrolyte during the battery charge and discharge process, prevent the decomposition of the electrolyte, and improve the safety and reliability of the magnesium battery. This functionalized coating enables the magnesium battery to have a longer cycle life and higher energy density.
[0022] 3. Through the optimized design of the negative electrode material of the magnesium battery, the present invention successfully overcomes the limitations of the traditional pure magnesium foil system in the magnesium battery. The tetrapyrrole compounds can enhance the stability of the magnesium electrode, slow down the corrosion and hydrogen evolution reaction of the magnesium metal, and promote the uniform deposition of magnesium ions on the electrode surface by interacting with the metal ions on the surface of the magnesium metal. In addition, the tetrapyrrole compounds have a high degree of molecular structure adjustability, and their compatibility with the electrolyte and the negative electrode material can be regulated by chemical modification, thereby optimizing the overall performance of the magnesium battery. Therefore, the coating modification based on tetrapyrrole compounds not only helps to improve the electrochemical performance of the magnesium negative electrode, but also has the potential to increase battery life, improve energy efficiency and reduce energy loss.
[0023] 4. The present invention preferably uses phthalocyanine compounds, which form a stable organic layer with the surface of the magnesium negative electrode to prevent external harmful substances (such as moisture and oxygen) from penetrating into the negative electrode, thereby avoiding corrosion of the magnesium negative electrode. At the same time, the metal center of the phthalocyanine compound interacts with magnesium metal to form a mixed layer of other metals-Zn, optimizes the deposition / dissolution behavior of magnesium ions, reduces the formation of dendrites, and improves the safety and performance of the battery. The binder combines with the phthalocyanine compound to enhance the mechanical strength and stability of the film layer, avoid peeling or cracking of the film layer, and maintain the integrity of the magnesium negative electrode interface.
[0024] 5. The present invention preferably uses polyvinylidene fluoride (PVDF) as a binder and N-methylpyrrolidone (NMP) as a solvent, which can effectively optimize the uniformity and stability of the coating. PVDF is a polymer material with excellent chemical stability and electrical insulation, which can ensure that the magnesium negative electrode material has good mechanical strength and stability during the charge and discharge process. NMP is used as a solvent to dissolve PVDF and form a uniform coating with tetrapyrrole compounds. The use of PVDF enhances the adhesion of the coating, ensures that the tetrapyrrole compounds are uniformly attached to the surface of the magnesium negative electrode, and effectively improves the durability of the coating. This combination can not only improve the compatibility of magnesium metal and electrolyte, reduce side reactions, but also maintain a high cycle stability during the charge and discharge process. By optimizing the ratio of PVDF and NMP, the present invention can simplify the preparation process while ensuring the stability of the coating, thereby improving the overall performance and service life of the magnesium battery. .
[0025] 6. The present invention can improve the deposition rate of magnesium ions and optimize the charge and discharge process of magnesium batteries by introducing tetrapyrrole compounds and binders on the negative electrode surface. In particular, during the charge and discharge cycle, magnesium ions will transfer between adjacent CN groups as coordination bonds are formed and cleaved. The magnesium battery negative electrode material based on the tetrapyrrole compound coating of the present invention is simple and feasible, low in cost, and has few preparation process steps and simple operation, and is suitable for large-scale promotion and production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a long cycle performance diagram of a Mg / / Mg symmetrical battery assembled with the negative electrode material in Example 1;
[0027] Figure 2 is a coulombic efficiency diagram of a Mg / / Cu asymmetric battery assembled with the negative electrode materials in Example 1 and Comparative Example 1;
[0028] Figure 3 The capacity-voltage curves of the Mg / / Ti asymmetric battery assembled with the negative electrode materials in Example 1 and Comparative Example 1;
[0029] Figure 4 is a coulombic efficiency diagram of a Mg / / Cu asymmetric battery assembled with the negative electrode materials in Examples 5, 6, and 7;
[0030] Figure 5 It is the wetting angle of the negative electrode material in Example 1 and Comparative Example 1 to deionized water. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1-8:
[0033] This group of embodiments provides a series of interface treatment methods for magnesium battery negative electrode materials, the method comprising mixing a tetrapyrrole compound, a binder and an organic solvent and stirring the mixture to obtain an interface treatment material, which is evenly spin-coated on the surface of a magnesium foil facing the positive electrode, and then vacuum drying the obtained magnesium foil at 80°C to dry the solvent to obtain a modified magnesium negative electrode, and the thickness of the dried interface treatment material is 5-50 μm.
[0034] The dosage of each raw material and the preparation process are shown in Table 1.
[0035] Table 1
[0036]
[0037]
[0038] Comparative Examples 1-3:
[0039] Pure magnesium foil is used as the negative electrode without interface treatment. The difference between different comparative examples lies in the different electrolytes used in preparing the batteries. The specific selection is shown in Table 1.
[0040] Test example:
[0041] (1) Overpotential test
[0042] The magnesium negative electrode coated with the tetrapyrrole compound coating described in Examples 1-8 and the untreated magnesium negative electrode of Comparative Examples 1-3 were tested by assembling CR2032 button batteries in the overpotential test. Polished magnesium sheets were used for both the working electrode and the counter electrode, and 120 μm of electrolyte was dripped onto the glass fiber (the types of electrolytes used in each embodiment and comparative example are shown in Table 1), and CR2032 button batteries were assembled in a glove box with water and oxygen contents less than 0.1 ppm. The assembled Mg / / Mg symmetrical battery was left to stand for 24 hours and then subjected to a constant current charge and discharge test on the Wuhan Land charge and discharge test system. The test procedure was to discharge for 30 minutes, charge for 30 minutes, and repeat the charge and discharge. The current density was 0.1-0.5 mA cm -2 .
[0043] The overpotential test results are shown in Table 2. The test results show that, compared with the pure magnesium foil magnesium battery negative electrode material, the symmetrical battery assembled with the negative electrode material of the tetrapyrrole compound coating exhibits lower overpotential and longer cycle life. Comparison between Example 1 and other examples shows that when the thickness of the tetrapyrrole compound coating is 10 μm, the symmetrical battery can stably operate for 650 h (such as 0.06 V) at a low deposition potential. Figure 1 As shown in Comparative Example 1, when the magnesium negative electrode is not modified in any way, the overpotential increases significantly.
[0044] Table 2 Coulomb efficiency and overpotential test results
[0045] Coulomb efficiency / % Overpotential / mV Example 1 99.5% 0.06V Example 2 92.4% 0.20V Example 3 99.0% 0.25V Example 4 99.1% 0.25V Example 5 99.4% 0.20V Example 6 92.1% 0.20V Example 7 99.1% 0.25V Example 8 99.1% 0.25V Comparative Example 1 98.0% 0.10V Comparative Example 2 80.0% 0.40V Comparative Example 3 82.1% 0.40V
[0046] (2) Coulomb efficiency test
[0047] The magnesium negative electrode coated with the tetrapyrrole compound coating described in Examples 1-8 and the untreated magnesium negative electrode of Comparative Examples 1-3 were tested by assembling CR2032 button batteries in the overpotential test. A polished magnesium sheet was used as the working electrode, and a copper foil or titanium foil was used as the counter electrode. 120 μm electrolyte was dripped on the glass fiber (the types of electrolytes used in each embodiment and comparative example are shown in Table 1), and CR2032 button batteries were assembled in a glove box with water and oxygen contents less than 0.1 ppm. The assembled Mg / / Cu and Mg / / Ti asymmetric batteries were left to stand for 24 hours and then tested on the Wuhan Land charge and discharge test system. The test program was first set to discharge for 1 hour, and a magnesium deposition reaction occurred on the working electrode with a current density of 0.1-0.5 mAcm -2 ; Then the voltage is controlled to charge to 0.8V. The charging process corresponds to the dissolution reaction of magnesium deposited on the working electrode, and the current density is 0.1-0.5mAcm -2 The test results are shown in Table 2.
[0048] In addition, the CR2032 type Mg / / Cu asymmetric battery assembled with the APC electrolyte in Example 1 can stably work for 600 hours with a coulombic efficiency of 99.4%; the electrolyte in Comparative Example 1 can only circulate for 150 hours (e.g. Figure 2 As shown). Example 1 and Comparative Example 1 were used to assemble a CR2032 type Mg / / Ti asymmetric battery (as shown Figure 3 As shown in the time-voltage curve, it can be observed that the negative electrode material coated with the tetrapyrrole compound exhibits low overpotentials of 0.15V and 0.06V and a high coulombic efficiency of 99.3% in the first cycle and 100 cycles, which is significantly better than Comparative Example 1.
[0049] In order to explore the universality of tetrapyrrole compound coating negative electrode materials, CR2032 type Mg / / Cu asymmetric batteries were assembled with different electrolytes in Examples 5, 6, and 7. 3 SO 3 ) 2 The coulombic efficiency of the battery assembled with the MACC-based electrolyte was 76.2% after 600 h of cycling; the battery assembled with the MACC-based electrolyte experienced a rapid decay after 200 h (e.g. Figure 4 shown).
[0050] (3) Hydrophobicity of the artificial interface layer
[0051] Example 1 and Comparative Example 1 were used as negative electrode materials for magnesium batteries. Deionized water was dripped onto them respectively to conduct wetting angle tests. The results are as follows: Figure 5 As shown. It can be observed that the wetting angle of the negative electrode material coated with tetrapyrrole compounds is greater than 116.556°, showing obvious hydrophobicity and inhibiting the side reaction between metal magnesium and water. However, pure metal magnesium shows hydrophilicity, with a wetting angle of 55.440° and bubbles can be observed on the surface, proving that metal magnesium reacts when in contact with water.
[0052] (4) Tightness of the artificial interface layer
[0053] In order to better evaluate the compactness of artificial SEI, the relative compactness density (rρ c ), a new dimensionless number is proposed, which is derived from the definition of density (ρ). Usually, density (ρ) is defined as
[0054] ρ=mv=msl
[0055] Where m, s and l represent the mass, bottom area and height of the test object respectively. The same standard is maintained for the artificial interface layer. Therefore, ρ is proportional to m and l. According to the above derivation, rρ c The relationship is as follows:
[0056] rρ c =ml
[0057] where m and l represent the mass and thickness of the artificial SEI, respectively.
[0058] Therefore, for artificial SEI with similar composition, higher rρ c The value represents a denser film per unit volume. c The values of are calculated to be 0.34, 0.27, 0.22, 0.30, 0.24, 0.21, 0.26 and 0.18 respectively. The tetrapyrrole compound coating of Example 1 exhibits higher density and effectiveness in reducing side reactions, which is consistent with the wettability results.
[0059] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for treating the interface of a negative electrode material of a magnesium battery, characterized in that: The method comprises the steps of mixing a tetrapyrrole compound, a binder and an organic solvent to obtain an interface treatment material, evenly spin coating the interface treatment material on the surface of the negative electrode of a magnesium battery, and then drying the solvent.
2. The interface processing method according to claim 1, characterized in that: The negative electrode of the magnesium battery includes magnesium foil, aluminum foil, copper foil, magnesium alloy, and carbon-based materials; the tetrapyrrole compound includes one or more of phthalocyanine compounds, porphyrin compounds, and synthetic tetrapyrrole compounds.
3. The interface processing method according to claim 2, characterized in that: The phthalocyanine compound includes one or more of copper phthalocyanine, iron phthalocyanine, aluminum phthalocyanine, nickel phthalocyanine and zinc phthalocyanine.
4. The interface processing method according to claim 2, characterized in that: The porphyrin compound includes one or more of heme, chlorophyll, cobalt porphyrin and magnesium porphyrin.
5. The interface processing method according to claim 2, characterized in that: The synthetic tetrapyrrole compound comprises one or more of dimethylphthalocyanine, aromatic tetrapyrrole compound and bimetallic porphyrin.
6. The interface processing method according to claim 1, characterized in that: The binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol, polyurethane, polyacrylic acid, polytetrafluoroethylene, hydroxypropyl methylcellulose, gelatin, alginate, polyvinyl alcohol-polyvinyl pyrrolidone, and polystyrene-polymethacrylate.
7. The interface processing method according to claim 1, characterized in that: The organic solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, 1,4-dioxane, and acetonitrile.
8. The interface processing method according to claim 1, characterized in that: The concentration of the tetrapyrrole compound in the organic solvent is 5-10 mmol / L.
9. The interface processing method according to claim 1, characterized in that: The mass ratio of the tetrapyrrole compound to the binder is (5-10):
1.
10. The interface processing method according to claim 1, characterized in that: The coating thickness of the interface treatment material on the surface of the negative electrode of the magnesium battery is 5-50 μm.